Collateral Functions In Baitulmal Wal Tamwil (BMT) Positive Legal Perspective and Sharia Economic Law - Az-zulfi, Ulfi Zulfikar Faridhun (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2023)
Microfinance institutions in Indonesia are experiencing very rapid development with the existence of the Baitulmal Wal Tamwil (BMT) as a new breakthrough by offering financing products that are present in the midst of a lower-class economic society. The development of Baitulmal Wal Tamwil (BMT) today offers many products in financing. At Baitulmal Wal Tamwil (BMT) the financing offered includes: mudharabah financing (youth cheerful), mudharabah financing (equally cheerful), murobahah ceria, services (hiwalah Ceria), services (Ihrom Ceria), and policies (qord Ceria). This type of research belongs to the Normative Juridical type of research. This research aims to find out how the legal position of guarantees/collaterals in Baitulmal Wat Tamwil, Every financing in Baitulmal Wal Tamwil (BMT) requires collateral where the collateral is one of the legal conditions in the Baitulmal Wat Tamwil financing contract. This type of research belongs to the Normative Juridical type of research. This research aims to find out how the legal position of guarantees/collaterals in Baitulmal Wat Tamwil, Every financing in Baitulmal Wal Tamwil (BMT) requires collateral where the collateral is one of the legal conditions in the Baitulmal Wat Tamwil financing contract. So researchers want to examine the function of collateral in Baitulmal Wal Tamwil (BMT) in sharia economic law and positive law where collateral is often used as a problem and its legal requirements in financing transactions in the Baitulmal Wat Tamwil (BMT) microfinance institution.